PENGARUH STRATEGI GENIUS LEARNING TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMP NEGERI 5 PADANG TAHUN PELAJARAN 2011/2012 - Devi, Nice Syilvia; Rismen, Sefna; Aima, Zulfitri (STKIP PGRI Sumbar, 2013)
The research based on the math grade VII SMPN 5 Padang that still low because it does not focus on learning and the learning atmosphere was not conducive and teachers rarely provide a conclusion at the end of the study. This research aims to find out if the results of the study of mathematics student with implementing strategi Genius Learning better than on the results of learning math students that apply to conventional learning at Class VII SMPN 5 Padang.A kind of this research is research experiments, population in this research is all the student Class VII SMPN 5 Padang academic year 2011/2012 as many as six local. The sample in this research is grade VII.7 as class experiments and student VII.8 as the class of the control. Instrument in research is written in the form of essay test with reliability = 0.76. data analysis techniques used are test-t party.Analysis of data performed with the help of software MINITAB, obnaited P-value = 0,007 smaller than standard Î± = 0,05.When.So inferred result learned mathematics student by applying strategy Genius Learning is better than learning the math student who apply learning conventional on class VII SMPN 5 Padang.